1911
DOI: 10.5962/bhl.title.29410
|View full text |Cite
|
Sign up to set email alerts
|

The pastoral age in Australasia, by James Collier.

Abstract: Fae away in the South Seas, a hundred years ago, more or less, the humane British Government was engaged in making a social experiment that had an issue undreamt of by its benevolent originators. It sent out to the newly discovered wilds of New South Wales successive contingents of its convicted felons, not only from the natural desire of getting rid of its worst citizens, but also with the hope of reforming criminals who could, by no possible chance, be reformed in England. The design succeeded beyond the hop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

1980
1980
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…administration of labetalol lowers the resting arterial blood pressure as seen in the present study. This is a consistent finding in healthy subjects [9,181 and in hypertensive patients [8,[19][20][21], and is probably predominantly due to the a-receptor blocking part of labetalol as P-receptor blocking agents do not reduce the resting blood pressure acutely [22, 231. A marked decrease in the blood pressure and giddiness were seen in the upright position, probably elicited by venous pooling of blood due to the a-receptor blockade [24]. Orthostatic faintness after i.v.…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…administration of labetalol lowers the resting arterial blood pressure as seen in the present study. This is a consistent finding in healthy subjects [9,181 and in hypertensive patients [8,[19][20][21], and is probably predominantly due to the a-receptor blocking part of labetalol as P-receptor blocking agents do not reduce the resting blood pressure acutely [22, 231. A marked decrease in the blood pressure and giddiness were seen in the upright position, probably elicited by venous pooling of blood due to the a-receptor blockade [24]. Orthostatic faintness after i.v.…”
Section: Discussionsupporting
confidence: 59%
“…Likewise, in patients on long-term treatment with labetalol, postural faintness is an occasional side effect only (6, 7, 191. Conflicting results have been obtained as to the effect of labetalol on heart rate at rest [8,9,18,20,21], whereas all reports agree that labetalol reduces the heart rate response to exercise, where sympathetic tone is raised [8, 9, 18, 211. In the present study heart rate increased just after the labetalol injection, probably due to the a-receptor blockade [24,251). Later, during forearm exercise and in the recovery phase the fall in heart rate indicated that the P-receptor blockade had prevailed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…No statistically significant correlation between antibody level and opsonic activity was observed (r = 0.096, P = 0.404). [32]. The ability of a host to produce specific antibodies against capsular polysaccharides is constituted by the activation of B cells by crosslinking of surface antigen receptors in the absence of T cells.…”
Section: Subjectsmentioning
confidence: 99%
“…Paul Wambua et al Studied the viability of Natural fibers as a replacement to Synthetic fibers [16]. Collier [17] studied the effect of cotton fibers in rubber. Effect of fiber diameter on mechanics of rubber composites was studied by Zhang et al [18].…”
Section: Introductionmentioning
confidence: 99%